MENACrit: A theoretical framework to understand Middle Eastern and North African international student experiences - Mesouani, Hannah (Journal of International Students, 2026)
The United States has a centuries-long history of restricting immigration policies in response to perceived threats from global communities of color. Much like the Irish and Chinese were socially vilified and legally persecuted throughout the 19th and 20th centuries, the global MENA (Middle Eastern and North African) community faces discriminatory processes and deep-seated suspicion as they engage with the United States. International students from the MENA region are particularly vulnerable to these practices as they come to a new country to pursue an education that promises a financially secure future, often not just for them but for their loved ones back home. Without due consideration, international MENA students’ experiences with the double standards of their conditional whiteness are neither examined nor prioritized in scholarship or university processes and procedures. T